Design and operation of power systems with large amounts of wind power, IEA collaboration - Holttinen, Hannele (2013)
New R&D collaboration on 'Design and Operation of Power Systems with Large Amounts of Wind Power Production' has been formed in IEA Wind. The R&D task will collect and share information on the experience gained and the studies made on power system impacts of wind power, and review methodologies, tools and data used. This paper outlines the power system impacts of wind power, the national studies published and on-going and describes the goals of the international collaboration. There are dozens of studies made and ongoing related to cost of wind integration, however, the results are not easy to compare. An in-depth review of the studies is needed to draw conclusions on the range of integration costs for wind power. State-of-the art review process will seek for reasons behind the wide range of results for costs of wind integration-definitions for wind penetration, reserves and costs; different power system and load characteristics and operational rules; underlying assumptions on variability of wind etc.